Tinjauan Etika Kristen Atas Fenomena Disaster Joke Terkait Pandemi Covid-19 - Yohanes Krismantyo Susanta; Daniel Fajar Panuntun (HARVESTER: Jurnal Teologi dan Kepemimpinan Kristen, 2020)
The focus of this research is to provide an overview from the perspective of Christian ethics on the phenomenon of disaster joke related to the development and spread of Covid-19. The formulation of the problem from this research is how is the ethical view of Critic to disaster joke related to the spread of Covid-19? The purpose of this study is to find a Christian ethical perspective on the spread of disaster jokes associated with the spread of Covid-19. The benefits of this research are: giving contribution to every believer to be able to empathize in every ethical decision making towards disaster joke related to the spread of Covid-19. Using a qualitative approach, this research shows that the golden rule principles taught by the Lord Jesus must be owned and applied by believers. Disaster joke is a despicable act, without empathy for victims of Covid-19 as well as not something to be laughed at. Because attitudes and actions committed against others are a reflection of our attitudes and actions towards God the creator.